2021
DOI: 10.1109/tuffc.2021.3054716
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Acoustic Measurements in Cylindrical Shell Containers

Abstract: Acoustic time-of-flight (ToF) measurements enable noninvasive material characterization, acoustic imaging, and defect detection and are commonly used in industrial process control, biomedical devices, and national security. When characterizing a fluid contained in a cylinder or pipe, ToF measurements are hampered by guided waves, which propagate around the cylindrical shell walls and obscure the waves propagating through the interrogated fluid. We present a technique for overcoming this limitation based on a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…This has been done non-invasively in similar applications. In [19]- [21], transmission measurements were performed with singleelement transducers placed in diametrically opposite locations on a liquid-filled pipe to determine the water cut level and the sound speed of different oil-water mixtures. The measured signals contained information from the liquid as well as the pipe wall (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This has been done non-invasively in similar applications. In [19]- [21], transmission measurements were performed with singleelement transducers placed in diametrically opposite locations on a liquid-filled pipe to determine the water cut level and the sound speed of different oil-water mixtures. The measured signals contained information from the liquid as well as the pipe wall (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…While our preliminary analysis suggests that the quantitative parameters extracted here may be robust to these expansion/contraction changes within our current analysis window, future experiments involving coupled ultrasound measurements and detailed cell thickness assessments could provide a more comprehensive understanding, particularly in the context of potential aging effects. Furthermore, prior studies have examined ultrasonic methods in cylindrical structures like pipelines and fluid‐filled shells, demonstrating the effectiveness of these techniques in gathering internal information from such structures [73,74] …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, prior studies have examined ultrasonic methods in cylindrical structures like pipelines and fluid-filled shells, demonstrating the effectiveness of these techniques in gathering internal information from such structures. [73,74] Ultrasound propagation in intricate structures, like the "jelly roll" form of cylindrical batteries, presents significant complexities. The simulation employed in our study qualitatively elucidates the ultrasonic wave propagation mechanisms in cylindrical batteries under specific experimental conditions.…”
Section: Ultrasound Wave Propagationmentioning
confidence: 99%
“…In [ 18 , 19 ], it is proposed to measure the sound speed of the liquid inside a pipe using pulse-echo in a similar configuration to that shown in Figure 1 b, but a priori information about the pipe wall is needed to compensate for its effect on the measured signals. In [ 20 ], it was shown that transducer array-based clamp-on UFMs may use guided waves to invert for the necessary parameters of the pipe and the liquid without any a priori information.…”
Section: Introductionmentioning
confidence: 99%